Descriptive of peer social support of recipient students KIP - Murvi, Indah Miranti; Hariko, Rezki (Current Issues in Counseling, 2023)
Peer social support is very important for every period of adolescent development. Peer social support is existence, caring and people who can be relied upon, appreciate and love friends of their age. The background of this research is that peer social support is very important for students so that students feel loved, cared for, valued as part of a social group. This type of research is a quantitative research with a descriptive and correlational approach. The research respondents were students of SMA Negeri 6 Padang who received KIP assistance with a total sample of 147 students using the total sampling technique. This study aims to see how the peer social support of KIP recipient students at SMAN 6 Padang is described. The instrument used in this study was peer social support, while the data were analyzed using a descriptive analysis system. The results of the study show that peer social support at SMAN 6 Padang is in the "Moderate" category, which means that the results of this study are included in the good category. Therefore, peer social support can be increased by increasing social support in the social environment.